Phytochemical Assessment of Certain Seaweeds of Enteromorpha Species in Coastal Regions of Ramanathapuram, Tamil Nadu, India: Life Sciences-Botany - Sona, P. (International Journal of Life Science and Pharma Research, 2023)
Freshly dried seaweeds are being extensively consumed, particularly by peoples living in coastal areas. Enteromorpha algae are nutritious and low-calorie food rich in essential Amino acids, Fatty acids, Vitamins, Dietary fiber and Resistant protein of humans. E. prolifera has many nutritional compounds and polysaccharides that have attracted extensive interest due to their numerous biological activities. The current studies for uses some Phytochemical components such as Alkaloids, Flavonoids, Phenols, Proteins, free Amino acids, Saponins, Sterols, Terpenoids, Coumarin, Glycosides, Quinones and Tannins are evaluated on the chosen Enteromorpha intestinalis species, including E. flexuosa, E. intestinalis and E. prolifera. In addition, Protein, Carbohydrate, Fat and photosynthetic pigments like chlorophyll and carotenoids were also quantitatively determined.